Living under the sun: examination of proverbs and qoheleth - Frydrych, Tomáš (Supplements to Vetus Testamentum, 2002)
Preliminary material /Tomáš Frydrych -- Introduction /Tomáš Frydrych -- The Wisdom Enterprise /Tomáš Frydrych -- How Does the Sage Know? /Tomáš Frydrych -- The Sages, God and the World /Tomáš Frydrych -- The Human World /Tomáš Frydrych -- Living Wisely /Tomáš Frydrych -- Proverbs and Qoheleth in an Historical Context /Tomáš Frydrych -- Conclusions /Tomáš Frydrych -- Appendix /Tomáš Frydrych -- Selected Bibliography /Tomáš Frydrych -- Index Nominum /Tomáš Frydrych -- Index Locorum /Tomáš Frydrych.